Manajemen Nyeri Farmakologi pada Pasien Pasca Pembedahan Open Reduction Internal Fixation (Orif) Ekstermias Atas dengan General Anestesi - Tiara Rachmadina; Amik Muladi (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
Post-operative pain after upper extremity ORIF is complex, involving tissue damage, inflammation and nociceptive mechanisms that require a comprehensive pharmacological approach. The intensity of post-ORIF pain typically ranges from moderate to severe in the first 48-72 hours and can affect early mobilisation, respiratory function and the patient's physiological stress response. Research objective: To determine the pattern of analgesic use for pain management after upper extremity ORIF surgery under general anaesthesia at Pandan Arang Boyolali Hospital. Research Methods: This is a qualitative research with case study approach. Data was collected using quota sampling technique. The sample in this study amounted to 5 patients with inclusion criteria: upper extremity orthopaedic surgery patients who will undergo ORIF in the Central Surgical Installation of Pandan Arang Boyolali Hospital in April 2025, patients with general anaesthesia Laryngeal Mask Airway (LMA). Results: Based on the results of observations, it was found that the pattern of use of pharmacological pain management in patients after upper extremity ORIF surgery with general anaesthesia at Pandan Arang Boyolali Hospital was the administration of 100 mcg fentanyl and 4 mg ondansentrone dripped in 500 ml Tutofusin infusion for surgery with a duration of > 1 hour and a large incision area.